Cyber Teaching dan Ancaman Alienasi: Potret Kecil Keterasingan Mahasiswa di Tengah Pandemi Covid-19 - Fawziah Zahrawati; Andi Aras (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
The purpose of this study was to determine the impact of cyber teaching during the covid-19 pandemic, the threat of alienation experienced by students, and the solution. The method used is a qualitative method with the type of phenomenological research. The subjects of this study were students of Tadris Social Sciences Faculty of Tarbiyah IAIN Parepare. Data collection techniques are observation and interviews. The results show that cyber teaching offers efficiency and open access to information. However, it cannot be separated from negative affects, such as students think pragmatically, the occurrence of moral degradation, delinquency, and deviant acts. In addition, during the covid-19 pandemic, students spend a lot of time in front of the virtual world screen. This can alienate them. Disproportionate and assignments can lead students into a state of alienation. Students can become isolated figures both from themselves and their environment. They become figures who are not independent and not autonomous in learning. Therefore, humanist education is needed by making students active in the learning process. Keywords: alienation, Covid-19, cyber teaching, humanist education.